THE PHILOSOPHICAL MEANING OF THE MAKKALU DAPURENG TRADITION IN THE PERSPECTIVE OF MARRIAGE: A HARMONIZATION OF BUGIS–MAKASSAR CULTURAL VALUES AND THE PRINCIPLES OF ISLAMIC SACREDNESS. - Pebriyani Jasmin, Suriah; Hasnia; Sudirman; Sarsil; Mustafa (Institut Agama Islam Negeri Bone, 2025)
The Makkalu Dapureng tradition is one of the enduring cultural heritages of the Bugis-Makassar community, still actively practiced today, particularly in the context of marriage ceremonies. This tradition reflects the values of togetherness, mutual cooperation, and social solidarity that form the moral foundation of community life. Beyond its social dimension, Makkalu Dapureng embodies profound philosophical meanings closely related to the essence of marriage as both a spiritual and social bond. This article aims to explore the philosophical significance of Makkalu Dapureng from the perspective of marriage using a theological-normative and sociological approach. Theologically, the study traces Islamic values embedded in the tradition, such as the principles of ta’awun (mutual assistance), ukhuwah islamiyah (Islamic brotherhood), and the ideals of sakinah, mawaddah, and rahmah as the ultimate goals of family life. Sociologically, it examines how this tradition strengthens social cohesion, fosters collective responsibility, and maintains the balance between individual and communal values. The findings reveal that Makkalu Dapureng functions not only as a social practice but also as a symbol of harmony between local cultural values and Islamic teachings. Its philosophical meaning lies in the moral messages of sincerity, loyalty, and togetherness, which serve as the main pillars of family life. Therefore, Makkalu Dapureng can be regarded as a tangible expression of the integration between culture and religion, reinforcing the sacredness of marriage within the Bugis-Makassar society.